The implementation of self-regulation in the communications and multimedia industry: balancing the interest of the industry and consumers / Nafisah Mohaidin, Norashikin Kamaruddin and Raz Ida Nadira Razali - Mohaidin, Nafisah; Kamaruddin, Norashikin; Razali, Raz Ida Nadira (2012)
This research focuses on the study on the implementation of self-regulation by an independent self-regulatory body set up by the Malaysian Communications and Multimedia Commission (MCMC), the Malaysian communications industry regulator in governing the multimedia and communication industry in Malaysia. Basically this study examines whether the self-regulation is better at protecting the interest of the industry or interest of the consumers, or that there is a balance between the two interests. This chapter is divided into 9 parts; (1 Research background, (2)research question, (3)research objectives, (4)research methodology, (5)scope of the research, (6)limitation to the research, (7)significance of the research, (8)literature review, and (9)Gantt chart. For a better understanding, all of the elements above were elaborated in this research.